PERILAKU KOMUNIKASI SUKU BAJO DALAM BERINTERAKSI DENGAN KOMUNITAS DARATAN DI DESA TERAPUNG KECAMATAN MAWASANGKA KABUPATEN BUTON Communication Behavior of Bajo Tribe in doing Interaction with Mainland Community in Floating Village Of Mawasangka District, Buton Regency - Yamran Sampeali yamran (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2011)
AbstractThis research aims to study the factors affecting the communication behavior of Bajo Tribe with mainland community infloating village of Mawasangka District, Buton Regency in South-East Sulawesi Province. The sample was selected usingpurposive sampling method consisting of 20 informants. They were 10 informants taken from Bajo tribe and 10 others weretaken from mainland community. The data were obtained through participative observation, in-depth interview, anddocumentation. The data were then analyzed using descriptive qualitative method. The result show that community behaviorof Bajo tribe with mainland community is based on customs and traditions and the needs related to their activities asfishermen. In general, community behavior of Bajo tribe is based on to what extent the strength and weakness of socialinteraction with mainland community. The stronger their interaction with mainland community , the bigger opportunity theoccurrence of new communication behavior which is identical to mainland community. Meanwhile, the factors affectingthe communication behavior of Bajo tribe in doing interaction with mainland community are education level, life patterns(kinship system, residence pattern, and marriage interactions (cooperation, accommodation, and assimilation).